ITI-Signals and Prelimbic Cortex Facilitate Avoidance Acquisition and Reduce Avoidance Latencies, Respectively, in Male WKY Rats - Beck, Kevin D.; Jiao, Xilu; Smith, Ian M.; Myers, Catherine E.; Pang, Kevin C. H.; Servatius, Richard J. (Frontiers in Behavioral Neuroscience, 2014)
As a model of anxiety disorder vulnerability, male Wistar-Kyoto (WKY) rats acquire lever-press avoidance behavior more readily than outbred Sprague Dawley rats, and their acquisition is enhanced by the presence of a discrete signal presented during the inter-trial intervals (ITIs), suggesting it is perceived as a safety signal. A series of experiments were conducted to determine if this is the case. Additional experiments investigated if the avoidance facilitation relies upon processing through medial prefrontal cortex (mPFC). The results suggest that the ITI-signal facilitates acquisition during the early stages of the avoidance acquisition process, when the rats are initially acquiring escape behavior and then transitioning to avoidance behavior. Post-avoidance introduction of the visual ITI-signal into other associative learning tasks failed to confirm that the visual stimulus had acquired the properties of a conditioned inhibitor. Shortening the signal from the entirety of the 3 min ITI to only the first 5 s of the 3 min ITI slowed acquisition during the first 4 sessions, suggesting the flashing light is not functioning as a feedback signal. The prelimbic (PL) cortex showed greater activation during the period of training when the transition from escape responding to avoidance responding occurs. Only combined PL+infralimbic cortex lesions modestly slowed avoidance acquisition, but PL cortex lesions slowed avoidance response latencies. Thus, the flashing light ITI-signal is not likely perceived as a safety signal nor is it serving as a feedback signal. The functional role of the PL cortex appears to be to increase the drive towards responding to the threat of the warning signal. Hence, avoidance susceptibility displayed by male WKY rats may be driven, in part, both by external stimuli (ITI signal) as well as by enhanced threat recognition to the warning signal via the PL cortex.